Combined non‐intubated anaesthesia and paravertebral nerve block in comparison with intubated anaesthesia in children undergoing video‐assisted thoracic surgery. Issue 6 (3rd April 2020) - Wei, Wei; Fan, Yanting; Liu, Wei; Zhao, Tianyun; Tian, Hang; Xu, Yingyi; Tan, Yonghong; Song, Xingrong; Ma, Daqing
Abstract : Background: This study is to investigate if non‐intubated anaesthesia combined with paravertebral nerve block (PVNB) can enhance recovery in children undergoing video‐assisted thoracic surgery (VATS). Methods: A randomized controlled trial including 60 patients aged 3 to 8 years old who underwent elective VATS was performed. They were randomly assigned to receive non‐intubated anaesthesia combined with PVNB or general anaesthesia with tracheal intubation (1:1 ratio). The primary outcome was the length of postoperative in‐hospital stay. The secondary outcomes included emergence time, the incidence of emergence delirium, time to first feeding, time to first out‐of‐bed activity, pain score and in‐hospital complications. Results: The non‐intubated group had shorter postoperative in‐hospital stay than the control group (4 days [IQR, 4‐6] vs 5 days [IQR, 5‐8], 95% CI 0‐2; P = .013). When compared to the control group, the incidence of emergence delirium (odds ratio [OR] 3.39, 95% CI 1.01‐11.41; P = .043), emergence time, duration in the PACU, time to first eating food, first out‐of‐bed activity, pain score and consumption of sufentanil (at 6 and 12 hours after surgery) were decreased in the intervention group. In contrast, the incidence of airway complications was higher in the control than the intervention group (27.6% vs 6.9%, P = .037). There was no statistical significance in the occurrence of PONV, pneumothorax and other complications between the two groups. Conclusions: Non‐intubated anaesthesia combined with PVNB enhances recovery in paediatric patients for video‐assisted thoracic surgery although further multi‐centre study is needed.